Boosting productivity for inclusive growth in Japan - Jones, Randall (OECD Economics Department Working Papers, 2017)
Never in the past 30 years has productivity growth been lower than since the 2008 global financial crisis, and never has income inequality been higher than it is today in Japan, and in the OECD area. The two challenges have some common origins, including a widening productivity and wage gap between leading firms and those that are lagging. This creates scope for positive synergy between policies to promote productivity and inclusive growth. Exit policy should be improved to facilitate the closure of non-viable firms, whose survival hampers the growth of viable firms in Japan. This would also increase firm entry, along with policies to promote entrepreneurship. The growing gap between small and medium-sized enterprises and large firms also needs to be addressed. Breaking down labour market dualism, which limits human capital accumulation by non-regular workers and contributes to earnings and income inequality, is also a priority. Finally, ensuring appropriate skills, including those needed for digitalisation, would help support higher productivity and inclusive growth. This Working Paper relates to the 2017 OECD Economic Survey of Japan (www.oecd.org/eco/surveys/economic-survey-japan.htm)